Administrative law / by K.K.Jayashankar and Philip Johnson - Jayashankar, K.K (Delhi, 2011)
Administrative law is the body of law that governs the activities of administrative agencies of government. Government. agency action can include rulemaking, adjudication, or the enforcement of a specific regulatory agenda. Administrative law is considered a branch of public law. It deals with the decision making of administrative units of government that are part of a national regulatory scheme in such areas as police law, international trade, manufacturing, the environment, taxation, broadcasting, immigration and transport. Administrative law expanded greatly during the twentieth century. This book covers all aspects and dimensions in the light of latest developments in the field of administrative law including the concept and concerns of global administrative law.
Keywords: Administrative - Law